2012
DOI: 10.1097/mao.0b013e31825f2387
|View full text |Cite
|
Sign up to set email alerts
|

Method and Reproducibility of a Standardized Ossiculoplasty Technique

Abstract: Short-term data suggest that this standardized technique of ossiculoplasty leads to predictable hearing outcomes and seems to be reproducible by an experienced otologist with only limited specific instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The titles were initially screened for inclusion resulting in further consideration of 485 publications. After screening of abstracts and then full‐text articles, 153 articles were selected for inclusion …”
Section: Resultsmentioning
confidence: 99%
“…The titles were initially screened for inclusion resulting in further consideration of 485 publications. After screening of abstracts and then full‐text articles, 153 articles were selected for inclusion …”
Section: Resultsmentioning
confidence: 99%
“…The main objective of surgical management of COM is the achievement of a dry and safe ear, the interruption of recurrent ear drainage and, on the other hand, the improvement of hearing. Therefore, tympanic membrane integrity and the ossicular chain status are important (8,12). The status of the ossicular chain as a determinant factor of hearing outcome has been somehow controversial in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Ossiculoplasty results reported in the literature have been variable and inconsistent. 12 This inconsistency is a reflection of the many variables likely to play a role in ossiculoplasty outcomes, including the underlying middleear pathology, the status of the Eustachian tube, surgical techniques, prostheses design, and patient factors. 4,[13][14][15][16][17][18][19][20][21] Furthermore, published data differ among studies with regard to the studied population, outcome measures reported, and follow-up periods.…”
Section: Discussionmentioning
confidence: 99%